"Being colorblind is one of the worst things": White teachers' attitudes and ethnic‐racial socialization in a rural elementary school. (10th December 2021) - Hazelbaker, Taylor; Mistry, Rashmita S.
Abstract: A phenomenological approach was used to explore White elementary school teachers' attitudes about and strategies for addressing ethnicity and race in their classrooms. Semi‐structured interviews were conducted with teachers ( N = 12) in first, third, and fifth grade, art, and English language learning classrooms at a racially diverse, rural elementary school in the Midwest United States. Results highlighted a paradox in teachers' attitudes and socialization. Teachers reported an appreciation for the school‐level ethnic‐racial diversity, while simultaneously endorsing a colorblind ideology. They incorporated conversations about ethnicity and race, but more frequently in reaction to holidays and student‐initiated questions and not as part of a more integrative curriculum. Additionally, teachers' attitudes and discussions about ethnicity and race intersected with religion. Findings highlight the need for professional development to support White teachers in examining their attitudes about ethnicity, race, and religion to move away from colorblindness and engage in anti‐bias and anti‐racist education.